The effect of disclosure on extraordinary returns of shares of iraqi companies - Shareef AL- Morshedi, Abbas Alwan; Rahi AL-Hisnawy, Salim Sallal (Opción, 2019)
The study aims to identify the impact of financial market reactions to the information content of the announcement of the dividend distribution via statistical methods to test the hypotheses through the T Test and the Mann–Whitney U test. The results proved null and void the hypothesis that the media content of the announcement of the dividends is statistically significant impact on the extraordinary returns of the shares of the study’s sample companies. In conclusion, the effect of the media content of the announcement of the dividend distribution on the extraordinary returns of the shares of companies was different.